Kinetic characterisation and mathematical modelling of the coenzyme A biosynthesis salvage pathway in Mycobacterium tuberculosis - Mocke, Leanie; Mocke, Leanie (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.